2017
DOI: 10.1111/hdi.12598
|View full text |Cite
|
Sign up to set email alerts
|

Low dialysate potassium concentration is associated with prolonged recovery time

Abstract: Introduction: Modifiable hemodialysis treatment parameters may impact patient reported outcomes, including recovery time. Answers to the recovery question may predict the impact of treatment parameters on clinical outcomes and health related quality of life. However, the reliability of answers to the recovery question after consecutive and nonconsecutive dialysis treatments in diverse populations has not been established.Objective: To assess the reliability of this instrument and to determine if recovery time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
3
24
1
Order By: Relevance
“…Conversely, Hussein et al [9] have demonstrated that a higher UFR was associated with a longer recovery time. Finally, in the study of Harford et al [15], any correlation between recovery time and UFR was found.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Conversely, Hussein et al [9] have demonstrated that a higher UFR was associated with a longer recovery time. Finally, in the study of Harford et al [15], any correlation between recovery time and UFR was found.…”
Section: Discussionmentioning
confidence: 81%
“…Data on the correlation between recovery time and UFR are few and conflicting [4,9,14,15]. In the study of Rayner et al [4], a longer recovery time was associated with greater intradialytic weight loss, longer dialysis session duration, and dialysate sodium concentration < 140 mEq/L.…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis recovery time (DRT) is a measure of post‐dialysis fatigue. DRT is often measured by asking the question, “How long does it take you to recover from dialysis?” This question has been found to be valid and responsive to change, as well as reliable at a variety of intervals . Internationally, it has been found that more than a quarter of maintenance HD patients report >6 hours of DRT …”
Section: Introductionmentioning
confidence: 99%
“…It is not known whether milder symptoms such as fatigue can occur following treatments in those patients already undergoing maintenance HD regularly. More rapid removal of vasoactive solutes altering hemodynamics and muscle contractility may also contribute to a feeling of fatigue . Dialysis modalities that involve longer or more frequent dialysis sessions allow for slower clearances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation